2001
DOI: 10.1007/s004290100205
|View full text |Cite
|
Sign up to set email alerts
|

The role of basic fibroblast growth factor in peripheral nerve regeneration

Abstract: In the peripheral nervous system regeneration and gradual functional restoration occur following peripheral nerve injury. Growth of regenerating axons depends on the presence of diffusible neurotrophic factors, in addition to the substratum. Neurotrophic factors that are involved in peripheral nerve regeneration include nerve growth factor, brain-derived neurotrophic factor, ciliary neurotrophic factor, glial cell line-derived neurotrophic factor, and interleukin-6. Recent functional and expression studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 62 publications
1
100
0
1
Order By: Relevance
“…After peripheral nerve injury, FGFR3 was upregulated in contrast to the other FGF-2 receptors (Ji et al, 1995;Grothe and Nikkhah, 2001). Furthermore, this receptor is crucially involved in the regulation of survival of sensory neurons after lesion but not during peripheral nerve development (Jungnickel et al, 2004a(Jungnickel et al, , 2005.…”
Section: Number Of Da Neurons Reduced In Fgfr3-deficient Micementioning
confidence: 97%
“…After peripheral nerve injury, FGFR3 was upregulated in contrast to the other FGF-2 receptors (Ji et al, 1995;Grothe and Nikkhah, 2001). Furthermore, this receptor is crucially involved in the regulation of survival of sensory neurons after lesion but not during peripheral nerve development (Jungnickel et al, 2004a(Jungnickel et al, , 2005.…”
Section: Number Of Da Neurons Reduced In Fgfr3-deficient Micementioning
confidence: 97%
“…Furthermore, it has been shown previously that entrapment of the low molecular weight (18-kDa) isoform of fibroblast growth factor-2 (FGF-2) in synthetic nerve guidance channels is able to enhance growth of myelinated and unmyelinated axons across long gaps significantly (Aebischer et al, 1989). With regard to the low and high molecular weight FGF-2 isoforms, it has been shown that the isoforms are differentially regulated following peripheral nerve injury, indicating differential physiological functions during peripheral nerve regeneration (for review, see: Grothe and Nikkhah, 2001). Non-resorbable silicone tubes were introduced as an experimental model for tubulization in peripheral nerve repair.…”
Section: Introductionmentioning
confidence: 99%
“…The half-life time of bFGF is relatively short (24), and cross-linked gelatin hydrogel (CGH) has been used to maintain the bioactivity of locally administered bFGF for an extended period (25,26). Furthermore, it has been reported that bFGF has effects on the central nervous system (27,28) and peripheral nervous system (29,30). However, the effects of bFGF on diabetic neuropathy have not been investigated.…”
mentioning
confidence: 99%